Closure of mesenteric defects in laparoscopic gastric bypass: a multicentre, randomised, parallel, open-label trial. Issue 10026 (2nd April 2016) - Stenberg, Erik; Szabo, Eva; Ågren, Göran; Ottosson, Johan; Marsk, Richard; Lönroth, Hans; Boman, Lars; Magnuson, Anders; Thorell, Anders; Näslund, Ingmar
Summary: Background: Small bowel obstruction due to internal hernia is a common and potentially serious complication after laparoscopic gastric bypass surgery. Whether closure of surgically created mesenteric defects might reduce the incidence is unknown, so we did a large randomised trial to investigate. Method: This study was a multicentre, randomised trial with a two-arm, parallel design done at 12 centres for bariatric surgery in Sweden. Patients planned for laparoscopic gastric bypass surgery at any of the participating centres were offered inclusion. During the operation, a concealed envelope was opened and the patient was randomly assigned to either closure of mesenteric defects beneath the jejunojejunostomy and at Petersen's space or non-closure. After surgery, assignment was open label. The main outcomes were reoperation for small bowel obstruction and severe postoperative complications. Outcome data and safety were analysed in the intention-to-treat population. This trial is registered withClinicalTrials.gov, numberNCT01137201 . Findings: Between May 1, 2010, and Nov 14, 2011, 2507 patients were recruited to the study and randomly assigned to closure of the mesenteric defects (n=1259) or non-closure (n=1248). 2503 (99·8%) patients had follow-up for severe postoperative complications at day 30 and 2482 (99·0%) patients had follow-up for reoperation due to small bowel obstruction at 25 months. At 3 years after surgery, the cumulative incidence of reoperation because of small bowel obstruction was significantly reduced in the closure group (cumulative probability 0·055 for closure vs 0·102 for non-closure, hazard ratio 0·56, 95% CI 0·41–0·76, p=0·0002). Closure of mesenteric defects increased the risk for severe postoperative complications (54 [4·3%] for closure vs 35 [2·8%] for non-closure, odds ratio 1·55, 95% CI 1·01–2·39, p=0·044), mainly because of kinking of the jejunojejunostomy. Interpretation: The results of our study support the routine closure of the mesenteric defects in laparoscopic gastric bypass surgery. However, closure of the mesenteric defects might be associated with increased risk of early small bowel obstruction caused by kinking of the jejunojejunostomy. Funding: Örebro County Council, Stockholm City Council, and the Erling-Persson Family Foundation.